Optimization of Ethanol Production from Mango Peels using Response Surface Methodology - Oh , P.C. (2014)
This study aims to optimize bioethanol production from mango peels using Response Surface Methodology (RSM). The effect of temperature (25–40 deg C), yeast concentration (6–14 g/ml) and fermentation time (48–96 hours) on bioethanol yield was investigated. Prior to the fermentation process, mango peels were treated with 0.25–1% (w/v) sulphuric acid. Optimum glucose yield was obtained at 0.25% (w/v) sulphuric acid. RSM using 3-factor 2-level central composite design (CCD) was employed to evaluate and optimize the synthesis parameters. Based on numerical optimization, the optimum fermentation conditions were at 38 deg C using 6 g/ml yeast for 48 hours, giving a yield of 7.34 g/ml bioethanol.